Polycystic Disease of the Kidneys with special reference to its Clinical features, Radiological diagnosis and Genetic Nature - de Villiers, Jacquez Charl (Department of Human Biology, 2020)
This work on polycystic disease of the kidney commenced while the author was engaged in general practice in Swellendam, in the South Western Cape from 1953-1956. Within a period of a year three patients, suffering from this disease, were seen. They were questioned about their family-relationship but they denied any such association. It was regarded as highly unlikely that three patients with a relatively rare disease, should be found in a population existing between those patients. The genealogy of each patient was worked out and when this information was bought together, it was found that they were fairly closely related. This was the first experience that the information obtained from a patient about his family may not be reliable, not even in a small, fairly closed community. As the family become known to the author the members were systematically investigated for polycystic kidney disease and an attempt was made to determine how many individuals were affected and i how many generations.